2023
DOI: 10.1177/00220426231151377
|View full text |Cite
|
Sign up to set email alerts
|

Injecting Alone. The Importance of Perceived Safety, Stigma and Pleasure for Solitary Injecting

Abstract: Many people who inject drugs (PWID) inject when they are alone which increases the risk for drug-related mortality, and the majority of overdose-related deaths occur among solitary users in residential environments. Drawing on qualitative data from interviews with 80 PWID in Norway, this study explores the complex practices of solitary injecting. The analysis illustrates that the risk environments in which they participated involved high levels of distress, fear and stigma that made them prefer solitary inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The proximity between these spaces for people who use drugs and low-threshold services enhances access to life-saving treatment during overdoses, emphasizing the importance of urban, centralized locations 13,14 . Overdose deaths often occur alone in private residences 23,24 , but our study showed how outreach workers were also approached at the Bench with concerns for individuals who were socially connected to the Bench but not present.…”
Section: Discussionmentioning
confidence: 85%
“…The proximity between these spaces for people who use drugs and low-threshold services enhances access to life-saving treatment during overdoses, emphasizing the importance of urban, centralized locations 13,14 . Overdose deaths often occur alone in private residences 23,24 , but our study showed how outreach workers were also approached at the Bench with concerns for individuals who were socially connected to the Bench but not present.…”
Section: Discussionmentioning
confidence: 85%
“…Our study findings highlight the need for interventions that increase the possibility of a bystander witnessing an overdose, along with greater naloxone distribution, to reduce OODs. Recognizing the importance of social and environmental factors that influence settings for drug use, public health efforts may encompass destigmatizing drug use, reducing isolation, housing-focused interventions, education and overdose awareness events, public messaging, peer-to-peer witnessing, and social support to reduce solitary drug use and improve overdose response . Additionally, there are several interventions currently being piloted or launched to prevent OODs among people who use drugs alone.…”
Section: Discussionmentioning
confidence: 99%